Tutorials in molecular reaction dynamics - Brouard, M. (Mark); Vallance, Claire; Royal Society of Chemistry (Great Britain). (Cambridge Royal Society of Chemistry, 2010)
Subjects covered in this text on molecular reaction dynamics range from the more traditional topics, such as potential energy surfaces, to the more advanced and rapidly developing areas, such as femtochemistry and coherent control. Each chapter concludes with a selection of problems designed to test understanding.
Includes bibliographical references (p. 450-473) and index.
Keywords: Reaction mechanisms (Chemistry)